2019
DOI: 10.3847/1538-4357/ab211c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Complex Organic Molecules in Soft X-Ray Irradiated Ices

Abstract: We study the chemical evolution of H 2 O:CO:NH 3 ice mixtures irradiated with soft X-rays, in the range 250 − 1250 eV. We identify many nitrogen-bearing molecules such as e.g., OCN − , NH + 4 , HNCO, CH 3 CN, HCONH 2 , and NH 2 COCONH 2 . Several infrared features are compatible with glycine or its isomers.During the irradiation, we detected through mass spectroscopy many species desorbing the ice. Such findings support either the infrared identifications and reveal less abundant species with not clear infrare… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 88 publications
2
44
2
Order By: Relevance
“…Recently, another experimental study employing X-ray photolysis of NH 3 -rich ices have also observed the formation of OCN À , NH 4 + , HCONH 2 , and other species including some IR features compatible with glycine or its isomers. 26 Employing photons between 250 to 1250 eV (with maximum at 700 eV) and combined infrared measurements with mass The infrared analysis of organic residue at room temperature indicates the presence of even more complex species, including HMT (hexamethylenetetramine), carboxylic salts and amides. The presence of HMT, amides and related species in irradiated NH 3 -rich ices by strong ionizing eld was also observed by Pilling et al, 16 employing cosmic ray analogs with energies in the range of MeV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, another experimental study employing X-ray photolysis of NH 3 -rich ices have also observed the formation of OCN À , NH 4 + , HCONH 2 , and other species including some IR features compatible with glycine or its isomers. 26 Employing photons between 250 to 1250 eV (with maximum at 700 eV) and combined infrared measurements with mass The infrared analysis of organic residue at room temperature indicates the presence of even more complex species, including HMT (hexamethylenetetramine), carboxylic salts and amides. The presence of HMT, amides and related species in irradiated NH 3 -rich ices by strong ionizing eld was also observed by Pilling et al, 16 employing cosmic ray analogs with energies in the range of MeV.…”
Section: Resultsmentioning
confidence: 99%
“…Ciaravella et al, 26 have determined the photodesorption yield for some new produced species, during X-ray photolysis of NH 3 -rich ices at 12 K, by employing a combination of mass spectrometry and infrared techniques. The authors, employing a broadband X-rays beam in the range between 250 and 1250 eV (with maximum at 700 eV) have obtained the following values, for some selected produced species (they detected more than 40 species), 1.94 Â 10 À5 and 3.17 Â 10 À5 for CH 3 NH 2 and HNCO, respectively.…”
Section: Chemical Equilibrium Aer Large Uencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been proposed that CH 2 (OH)CHO formation is boosted by ice irradiation (Biver et al, 2015). This irradiation can either be in the form of UV photons, X-rays, or cosmic rays, since all types of irradiation have the same effect on the final chemical composition of the ices (Muñoz Caro et al, 2014;de Marcellus et al, 2014;Meinert et al, 2016;Ciaravella et al, 2019). Although G + 0.693-0.027 is not close to any obvious source of radiation, this cloud is embedded in an environment where the cosmic-ray ionization rate is enhanced by factors 100-1000 (Goto et al, 2013).…”
mentioning
confidence: 99%
“…Our ongoing collaboration with the Palermo Observatory in Italy and the National Central University in Taiwan is devoted to study the effect of X-rays emitted by young stars in the ice. These experiments were conducted in the ISAC setup using a Palermo home-made X-ray source, and later at the National Synchrotron of Taiwan (NSRRC) to increase the flux of soft X-rays [40,44,48,49,50,51,52,53,54,55]. Meanwhile, we employed swift heavy ions provided by the French accelerator GANIL at Caen to reproduce cosmic ray impact in the ice [56].…”
Section: Review Of Experimental Resultsmentioning
confidence: 99%